Methodology of Teaching the Russian Language in Higher Education - Khadzhikurbanova Gulbahor Aslitdinovna (Zien Journals, 2022)
Like any science, the methodology of the Russian language has its own theme. The subject of his study is the process of mastering the native language in the learning environment (speech, writing, reading, grammar, phonetics, etc.). The methodology of the Russian language is intended for the formation of skills in the field of language, for studying the patterns of mastering systems. scientific concepts in grammar and other sections of linguistics. The results of this study form the fundamental basis for solving the problem.
Keywords: fundamental; grammar; methodology; Russian